Pandemics, Health Behavior and Tourism - PODVORICA, Ganimete; RRUSTEMI, Visar (Journal of Environmental Management and Tourism, 2020)
The current paper examines if respondents that take strict prevention measures against COVID-19, with higher monthly incomes and that have spent their summer vacations in Albania last year are significantly more likely to plan their summer vacations to Albania this summer relative to those that are neglecting prevention measures, have lower incomes and have not chosen Albania as their destination for summer vacations last year. The study employs a survey of 500 random respondents. A multivariate analysis indicated that scores of planning summer vacations were significantly associated with the present strict prevention behavior measures against COVID-19 indicating the existence of sufficient motivation for future behavior intentions. In contrasts, monthly income is not a predictor for planning summer vacations. Finally, the correlation is positive between respondent’s previous experience to touristic destinations in Albania last year and planning summer vacations this year. Hence, it is recommended a thoughtful examination of respondents’ health behaviors, needs, wants and collaboration in shaping the better future of public health that is a shared one.